2020
DOI: 10.1371/journal.ppat.1009169
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed Human Cytomegalovirus gB nanoparticle vaccine with improved immunogenicity

Abstract: Human cytomegalovirus (HCMV) is the primary viral cause of congenital birth defects and causes significant morbidity and mortality in immune-suppressed transplant recipients. Despite considerable efforts in vaccine development, HCMV infection still represents an unmet clinical need. In recent phase II trials, a MF59-adjuvanted gB vaccine showed only modest efficacy in preventing infection. These findings might be attributed to low level of antibodies (Abs) with a neutralizing activity induced by this vaccine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Our data suggest that variants carrying R267K may promote this protective response. This is pertinent because gB is under investigation as an HCMV vaccine candidate ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that variants carrying R267K may promote this protective response. This is pertinent because gB is under investigation as an HCMV vaccine candidate ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A second effort at targeting gB for vaccine development found that HCMV-neutralizing antibodies primarily targeted antigenic domain 5 [ 211 ]. Using this information, a nanoparticle vaccine was created that increased titers of neutralizing antibodies by 100-fold in comparison to gB extracellular domain vaccine [ 211 ], presumably by increasing the number of copies of antigen presented and by presenting the antigens in a well-ordered manner that may more closely resemble the pathogen surface [ 211 , 212 ].…”
Section: Vaccination Effortsmentioning
confidence: 99%
“…Based on HCMV and GPCMV gB alignment, the equivalent HCMV gB amino acids are 50 and 394 (for altered amino acids in gB GPCMV 59 and 383 respectively). Although antigenic domains have not been evaluated for GPCMV gB, the HCMV gB amino acids 50 and 394 are in AD2 and AD4 regions, respectively [21,54,55]. The potential AD2 region in GPCMV has poor conservation with HCMV but the change would likely be minor based on surrounding flanking charged sequences and the change from positive charge to polar (R→S).…”
Section: Impact Statementmentioning
confidence: 99%
“…The gB glycoprotein is an immunodominant antibody target and forms a trimeric complex in the virion [20]. HCMV gB has multiple antigenic domains (AD1-AD5) that contribute to the antibody response to the protein [21]. AD1 domain is immunodominant and necessary for gB oligomerization and AD1 sequence is conserved in various animal CMV gB [22,23].…”
Section: Introductionmentioning
confidence: 99%